Feminist Periodicals and Daily Life - Green, Barbara. author. aut Link
XI, 312 p. 10 illus.
Keywords: This volume uncovers the ideas concerning everyday life circulating in the burgeoning feminist periodical culture of Britain in the early twentieth century. Barbara Green explores the ways in which the feminist press used its correspondence columns, women’s pages, fashion columns and short fictions to display the quiet hum of everyday life that provided the backdrop to the more dramatic events of feminist activism such as street marches or protests. Positioning itself at the interface of periodical studies and everyday life studies, Feminist Periodicals and Daily Life illuminates the more elusive aspects of the periodical archive through a study of those periodical forms that are particularly well-suited to conveying the mundane. Feminist journalists such as Rebecca West, Teresa Billington-Greig, E. M. Delafield and Emmeline Pethick Lawrence provided new ways of conceptualizing the significance of domestic life and imagining new possibilities for daily routines.